Translator of Hindi Text to ISL and extension of ISL dictionary with WordNet - Vij, Paras (My University, 2016)
Sign Language is the basic source of communication for deaf people across the world. Sign Language is used by the deaf people to communicate with each other and also by their families and friends to communicate with them. Sign Language varies from place to place. America has American Sign Language, Britain has British Sign Language and India has Indian Sign Language. Sign Languages use arms, hands, body and facial expressions for communication. Each word has a different expression. It is a major linguistic challenge that the researchers have taken to build system which could facilitate the understanding of natural language. According to World Federation of Dead there are approximately 70 million deaf and dumb people in the world and 4 million dead people in India according to All India Federation of Deaf. Due to lack of linguistically annotated and well documented data on Indian Sign Language research on Indian Sign Language Linguistics is limited. In this thesis Hindi to Indian Sign Language with extension using Hindi WordNet system is developed. The system has been developed in Java which makes it accessible across different platforms. System takes Hindi Sentence as input and generates corresponding Indian Sign Language sentence. For converting Hindi to Indian Sign Language Hindi Dependency Parser is used which gives information about each word in sentence. After parsing each word is taken and Indian Sign Language grammar rules are applied. Words which do not pass grammar rules are removed from sentence. Words which passed grammar rules are then searched in database to find if we have signs for them. If a word has sign available it is copied into final Indian Sign Language sentence. If we do not have sign available for a word then we use WordNet to find a replacement for that word. WordNet returns synonyms for word. Each synonym is checked in our database to see if we have sign available for that synonym. If a synonym has sign available that word is replaced with synonym in final Indian Sign Language sentence. If no synonym is found which has sign available in our database then we mark word as Finger Spelled in our final sign language sentence. After processing each word final Indian Sign Language sentence is shown on the screen to user.
Master of Engineering-Computer Science
Keywords: Sign Language; Parser